2022
DOI: 10.1038/s41598-022-26322-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiling in dogs with dilated cardiomyopathy eating non-traditional or traditional diets and in healthy controls

Abstract: Dilated cardiomyopathy (DCM), caused by genetic and environmental factors, usually progresses to heart failure, a major cause of death in elderly people. A diet-associated form of DCM was recently identified in pet dogs eating non-traditional (NT) diets. To identify potential dietary causes, we analyzed metabolomic signatures and gene set/pathway enrichment in (1) all dogs based on disease, diet, and their interactions and (2) dogs with DCM based on diet. Metabolomic analysis was performed in 38 dogs with DCM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…Zhe Wang et al also reported that linoleante is associated with increased risk of coronary heart disease ( 47 ). Moreover, linolenate was found among the metabolites that differed significantly in dogs with dilated cardiomyopathy eating a non-traditional diet or a traditional diet ( 48 ). In addition, this metabolite was shown to be associated with urine albumin excretion rate ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhe Wang et al also reported that linoleante is associated with increased risk of coronary heart disease ( 47 ). Moreover, linolenate was found among the metabolites that differed significantly in dogs with dilated cardiomyopathy eating a non-traditional diet or a traditional diet ( 48 ). In addition, this metabolite was shown to be associated with urine albumin excretion rate ( 35 ).…”
Section: Discussionmentioning
confidence: 99%